Social control on the Sandwich Generation in the film “1 Kakak 7 Ponakan” - Bimo Aryo Mukti; Muh. Fatoni Rohman (Universitas Muhammadiyah Malang, 2025)
The phenomenon known as the Sandwich Generation is prevalent in contemporary society, particularly among individuals born into low-income families who bear the responsibility of supporting other family members. This generation is frequently linked to deviant behaviour owing to a lack of social control. The present study seeks to examine the mechanisms of social control within the Sandwich Generation, as depicted in the film